Tata Kelola Perusahaan, Volatilitas, dan Investasi Penelitian dan Pengembangan pada Masa Pandemi COVID-19 - Evadine, Rebecca; Barents, Edgina (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Research and Development (R&D) investment has long been recognized as an important driver of innovation, competitiveness, and long-term economic growth. However, the COVID-19 pandemic created unprecedented uncertainty that altered corporate investment priorities and changed the way organizations allocate resources for innovation. This study aims to examine the relationship between corporate governance, market volatility, and R&D investment during the COVID-19 pandemic while exploring how the crisis reshaped corporate innovation strategies. The study employs a descriptive qualitative approach through a narrative literature review by synthesizing findings from previous studies related to corporate governance, volatility, R&D investment, and the economic consequences of the pandemic. The findings indicate that the pandemic increased economic and market volatility, disrupted global supply chains, and forced companies to reassess their investment decisions. Under these conditions, R&D was no longer viewed solely as a long-term innovation activity but also as a strategic mechanism to enhance organizational resilience. Investment priorities shifted toward digital transformation, health-related innovation, and technologies that support business continuity. Furthermore, effective corporate governance played an important role in maintaining the quality of investment decisions and enabling firms to adapt their innovation strategies under uncertain conditions. This study contributes by providing an integrated perspective on the interaction between corporate governance, volatility, and R&D investment during periods of crisis. The findings offer practical implications for managers and policymakers in designing more adaptive and resilient innovation policies for future disruptions.